Novel Surgical Approach for Decompression of the Scalene Triangle in Neurogenic Thoracic Outlet Syndrome - Hagan, Robert R.; Ricci, Joseph A.; Eberlin, Kyle R. (Journal of Reconstructive Microsurgery, 2018)
Thoracic outlet syndrome (TOS) is a cause of upper extremity and shoulder dysfunction. TOS can present with a wide range of symptoms due to compression of the brachial plexus or its branches during their passage through the cervicothoracobrachial region or scalene triangle. There are three types of TOS: arterial, venous, and neurogenic. Neurogenic TOS (nTOS) is by far the most frequent type and represents more than 95% of all cases. Historically, surgical intervention for all types of TOS has evolved based on the treatment for a vascular etiology and has typically included a first rib resection. Despite nTOS being by far the more common type, most previous interventions have not considered treatment via peripheral nerve decompression.We describe surgical treatment of nTOS, performed on an outpatient basis, which focuses on the surgical decompression of the structures associated with the scalene triangle in conjunction with release of the pectoralis minor insertion through limited incisions. The procedure avoids the morbidity associated with first rib resection and is successful in ameliorating nTOS symptoms. Further, we propose a nomenclature shift to scalene triangle syndrome (STS) to reflect the nerve and arterial compressions needing to be addressed.
Keywords: neurogenic thoracic outlet syndrome; peripheral nerve; scalene triangle syndrome